Risk-Stratification of Children Presenting to Ambulatory Paediatrics with First-Onset Seizures: Should We Order an Urgent CT Brain?. (18th October 2019) - Brugman, Jaanri; Solomons, Regan Shane; Lombard, Carl; Redfern, Andrew; Du Plessis, Anne-Marie
Abstract: Introduction: A computed tomography (CT) brain scan is an often-utilised emergency department imaging modality to detect emergent intra-cranial pathology in a child with a first seizure. Identifying children at low risk of having a clinically significant intra-cranial abnormality could prevent unnecessary radiation exposure and contrast/sedation-related risks. Objectives: To identify clinical variables which could predict clinically significant CT brain abnormalities and use recursive partitioning analysis to define a low-risk group of children in whom emergent CT brain can be deferred. Methods: Retrospective cross-sectional review of 468 children who underwent emergent CT brain after presenting to a low- and middle-income paediatric emergency department following first seizure. Results: In total 133/468 (28.4%) of CT brain scans had clinically significant abnormalities. Failure to return to neurological baseline and focal neurological deficit persisting >36 h had statistical significance in a multiple regression analysis. Recursive partitioning analysis, applied to a subgroup without suspected tuberculous meningitis ( n = 414), classified 153 children aged between 6 months and 5 years, who had a normal neurological baseline, had returned to baseline post-seizure, and were not in status epilepticus, as non-clinically significant scans and 98% were correctly classified. Conclusion: Our study re-inforces the American Academy of Neurology recommendation that children with persistent post-ictal abnormal neurological status and/or post-ictal focal deficit be prioritised for emergent CT brain. Having excluded children with suspected tuberculous meningitis, the remaining subgroup aged 6 months to 5 years presenting with a non-status first seizure, normal neurological baseline and return to baseline post-seizure, are at very low risk of having a clinically significant CT brain abnormality.